PROFILE OF PEDIATRIC MALIGNANCIES AT A RURAL CENTRE - A TEN YEAR STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Pediatric malignancies represent a significant cause of morbidity and mortality in children worldwide, with variations in incidence and spectrum between urban and rural populations. Data from rural centers in developing countries remain limited. Aims and Objectives: This study aimed to evaluate the clinicopathological profile of pediatric malignancies over a ten-year period at a rural tertiary care center. Materials and Methods: This retrospective observational study was conducted over one year at Mahatma Gandhi Institute of Medical Sciences, Sevagram, Dist. Wardha, Maharashtra including 142 pediatric patients (0–18 years) with malignancies. Data were analyzed for age, gender, type of malignancy, clinical features, and stage at presentation to assess the pattern of pediatric cancers. Results: The study showed that pediatric malignancies were most common in the 6–10 years age group with male predominance. Hematological malignancies, especially ALL, were most frequent, with fever and pallor as common symptoms. Most patients presented at an advanced stage, indicating delayed diagnosis and need for early detection. Conclusion: The study highlights that pediatric malignancies in rural settings are predominantly hematological in nature, with acute leukemias being the most frequent. Early recognition of symptoms and improved diagnostic facilities at rural centers can aid in timely diagnosis and management. Strengthening awareness and healthcare infrastructure is essential to improve outcomes in pediatric oncology in resource-limited settings.